2013
DOI: 10.4103/0301-4738.118455
|View full text |Cite
|
Sign up to set email alerts
|

Association of extensive myelinated nerve fibers and high degree myopia: Case report

Abstract: Unilateral extensive myelination of the peripapillary nerve fibers may be associated with anisometropic myopia, strabismus, and reduced vision. Myelination of optic nerve fibers terminate at lamina cribrosa. Yet in some patients, myelination progresses into the peripapillary retinal nerve fibers and may affect the visual acuity. In this report, we described 4 patients. All patients presented extensive peripapillary myelinated nerve fibers associated with myopic anisometropia. After routine ophthalmic and ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This means that a low degree of anisometropia is associated with better visual outcomes after the prescription of cycloplegic refraction findings and intensive occlusion therapy [ 4 ]. Strabismus in Straatsma syndrome is another factor associated with poor visual prognosis [ 4 , 7 ]. In both, our patient's initial BCVA was 0.1, with a high degree of anisometropia and similar spherical equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…This means that a low degree of anisometropia is associated with better visual outcomes after the prescription of cycloplegic refraction findings and intensive occlusion therapy [ 4 ]. Strabismus in Straatsma syndrome is another factor associated with poor visual prognosis [ 4 , 7 ]. In both, our patient's initial BCVA was 0.1, with a high degree of anisometropia and similar spherical equivalents.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in peripheral retina of myopic are predisposing factors for retinal detachment and include lattice degeneration, white-without-pressure, pigmentary degenerations, and retinal tears and holes. Association of extensive myelinated nerve fibers and high degree myopia have been reported [16]. Ellis et al [17] found that 83% of patients with myelinated retinal nerve fibers had myopia greater than 6 diopters.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive unilateral myelination of nerve fibers can be associated with high myopia and severe amblyopia, which unlike other forms of amblyopia is notoriously refractory to treatment. [ 5 ] In such patients, myelination surrounds most of the circumference of the disc.…”
mentioning
confidence: 99%